Migration and Integration Challenges of Muslim Immigrants in Europe Debating Policies and Cultural Approaches - Profanter, Annemarie; Maestri, Elena (Politics of Citizenship and Migration, 2021)
XVII, 289 p. 8 illus., 6 illus. in color.